Dynamics of glyphosate and AMPA in the soil surface layer of glyphosate-resistant crop cultivations in the loess Pampas of Argentina. (January 2019) - Bento, Célia P.M.; van der Hoeven, Siebrand; Yang, Xiaomei; Riksen, Michel M.J.P.M.; Mol, Hans G.J.; Ritsema, Coen J.; Geissen, Violette
Abstract: This study investigates the dynamics of glyphosate and AMPA in the soil surface layer of two fields growing glyphosate-resistant crops in the loess Pampas of Córdoba Province, Argentina. Glyphosate decay and AMPA formation/decay were studied after a single application, using decay kinetic models. Furthermore, glyphosate and AMPA concentrations were investigated in runoff to evaluate their off-site risk. During a 2.5-month study, cultivations of glyphosate-resistant soybean and maize received an application of 1.0 and 0.81 kg a.e. ha −1, respectively, of Roundup UltraMax © . Topsoil samples (0–1, 1–2 cm) were collected weekly (including before application) and analysed for glyphosate, AMPA and soil moisture (SM) contents. Runoff was collected from runoff plots (3 m 2 ) and weirs after 2 erosive rainfall events, and analysed for glyphosate and AMPA contents (water, eroded-sediment). Under both cultivations, background residues in soil before application were 0.27–0.42 mg kg −1 for glyphosate and 1.3–1.7 mg kg −1 for AMPA. In the soybean area, the single-first-order (SFO) model performed best for glyphosate decay. In the maize area, the bi-phasic Hockey-Stick (HS) model performed best for glyphosate decay, due to an abrupt change in SM regimes after high rainfall. Glyphosate half-life and DT90 were 6.0 and 19.8 days, respectively, in the soybean area, and 11.1 and 15.4 days, respectively, in the maize area. In the soybean area, 24% of the glyphosate was degraded to AMPA. In the maize area, it was only 5%. AMPA half-life and DT90 were 54.7 and 182 days, respectively, in the soybean area, and 71.0 and 236 days, respectively, in the maize area. Glyphosate and AMPA contents were 1.1–17.5 times higher in water-eroded sediment than in soil. We conclude that AMPA persists and may accumulate in soil, whereas both glyphosate and AMPA are prone to off-site transport with water erosion, representing a contamination risk for surface waters and adjacent fields. Graphical abstract: Image 1 Highlights: Glyphosate & AMPA dynamics in the soil surface layer of GR crop cultivations was studied. Glyphosate decay followed the SFO model in the soybean area, but the HS model in the maize area. AMPA formation and decay rates were lower than commonly found. Sheet erosion results in runoff with high glyphosate & AMPA contents adsorbed to eroded sediment. Decay is the dominant process describing glyphosate dynamics. Abstract : Glyphosate and AMPA dynamics in the soil surface layer of cultivation areas from the loess Pampas of Argentina show high risk of AMPA accumulation, while water erosion represents a high risk for their transport to off-target areas.